Glosa do uchwały Sądu Najwyższego z dnia 11 grudnia 2018 roku, III CZP 31/18 Odpis pisma procesowego zawierającego rozszerzenie powództwa nie podlega doręczeniu na podstawie art. 132 § 1 k.p.c. - Wójcik, Dominika (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The subject of the commentary is the resolution of the Supreme Court of 11 December 2018, III CZP 31/18 which states that in a situation where both parties are represented by professional representatives a copy of the letter containing the extension of the claim should be delivered to the defendant by the court. This issue has caused discrepancies in the case law of common courts and the jurisprudence of the Supreme Court. Therefore, the study analyzes the arguments presented by the Supreme Court in the justification of the said decision; additional circumstances are also cited, which, according to the author of the commentary, prove the legitimacy of the official notification extending the claim which will ensure the efficiency of the proceedings and will counteract legal uncertainty.
Keywords: civil proceedings; autonomous delivery; official notification; extension of the claim; professional representative